Optimal Cyclic Reflux Operational Policy for Ternary Mixtures Separation - Stojkovic, Marija (Sustainable Chemical Engineering, 2025)
The optimal control of a multicomponent batch distillation campaign with a variable reflux ratio, and an analysis of the influence of different parameters, have been presented. At first, the influence of initial mixture composition combined with the influence of the top pressure brought about: 1) a clear 'bang-bang' policy, which is easier to verify and apply in an industrial environment, and 2) time reduction by 14.07%. Furthermore, the influence of vapor boil-up showed that with the increase of vapor boil-up by 2.73 times, there is a significant increase in recovery rate by 27.55%, whilst a significant reduction of overall time horizon by 41.71% for total recovery. Finally, the influence of reboiler volume: with the doubling of reboiler volume, again, there is a significant increase in recovery rate by 32.98%, and, interestingly, the overall time horizon reduction is almost the same as in the previous case, as it gives 41.90% for total recovery. These results give flexibility in terms of process design: one can choose between different variable parameters to achieve the targeted recovery rate and/or final time.